The influence of airway supporting maneuvers on glottis view in pediatric fiberoptic bronchoscopy - Tarik Umutoglu; Ahmet Hakan Gedik; Mefkur Bakan; Ufuk Topuz; Hayrettin Daskaya; Erdogan Ozturk; Erkan Cakir; Ziya Salihoglu (Revista Brasileira de Anestesiologia, 2015)
ABSTRACTINTRODUCTION:Flexible fiber optic bronchoscopy is a valuable intervention for evaluation and management of respiratory diseases in both infants, pediatric and adult patients. The aim of this study is to investigate the influence of the airway supporting maneuvers on glottis view during pediatric flexible fiberoptic bronchoscopy.MATERIALS AND METHODS:In this randomized, controlled, crossover study; patients aged between 0 and 15 years who underwent flexible fiberoptic bronchoscopy procedure having American Society of Anesthesiologists I---II risk score were included. Patients having risk of difficult intubation, intubated or patients with tracheostomy, and patients with reduced neck mobility or having cautions for neck mobility were excluded from this study. After obtaining best glottic view at the neutral position, patients were positioned jaw trust with open mouth, jaw trust with teeth prottution, head tilt chin lift and triple airway maneuvers and best glottis scores were recorded.RESULTS:Total of 121 pediatric patients, 57 girls and 64 boys, were included in this study. Both jaw trust with open mouth and jaw trust with teeth prottution maneuvers improved the glottis view compared with neutral position (p < 0.05), but we did not observe any difference between jaw trust with open mouth and jaw trust with teeth prottution maneuvers (p > 0.05). Head tilt chin lift and triple airway maneuvers improved glottis view when compared with both jaw trust with open mouth and jaw trust with teeth prottution maneuvers and neutral position (p < 0.05); however we found no differences between head tilt chin lift and triple airway maneuvers (p > 0.05).